1999
DOI: 10.1038/sj.bjc.6690463
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomized study on the myeloprotective effect of melatonin in combination with carboplatin and etoposide in advanced lung cancer

Abstract: A significant myeloprotective effect of melatonin in mice treated with etoposide, cyclophosphamide or carboplatin has been reported. The present study was designed to evaluate if the same effect could be observed in patients receiving chemotherapy. Twenty previously untreated patients with inoperable lung cancer received two cycles of carboplatin (given at area under the curve 5 by the Calvert formula) on day 1 and etoposide (150 mg m −2 i.v.) on days 1–3 every 4 weeks. Melatonin 40 mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…(19,20,21,22,23,11,24,25,26,27,28,29,30,31,32, 33) Three independent randomized trials, including this trial, have been run. (34,35) It is noteworthy that all of the trials from Lissoni and colleagues have had positive outcomes and, as of yet, there have been no confirmatory publications from outside of his group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19,20,21,22,23,11,24,25,26,27,28,29,30,31,32, 33) Three independent randomized trials, including this trial, have been run. (34,35) It is noteworthy that all of the trials from Lissoni and colleagues have had positive outcomes and, as of yet, there have been no confirmatory publications from outside of his group.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20,21,22,23,11,24,25,26,27,28,29,30,31,32,33) Three independent randomized trials, including this trial, have been run. (34,35) It is noteworthy that all of the trials from Lissoni and colleagues have had positive outcomes and, as of yet, there have been no confirmatory publications from outside of his group.The difference could reflect a difference in the biological properties of the melatonin being used. Melatonin has very poor bioavailability, with approximately 15% absorption.…”
mentioning
confidence: 99%
“…[19][20][21] Even endogenous antioxidants, such as melatonin, might work to enhance chemotherapy, 22 but such findings have not consistently been reproduced. 23 Unfortunately, this is one of the many critical questions without a good answer at this time. Therefore, it would be prudent to advise patients undergoing chemotherapy or radiotherapy not to exceed the upper intake limits of the Dietary Reference Intakes for vitamin supplements and to avoid other nutritional supplements that contain antioxidant compounds.…”
Section: Nutrition During and After Cancer Treatmentmentioning
confidence: 99%
“…66 The study of Cerea et al 67 and many other studies [63][64][65][66]68,69 reported positive results regarding toxicity reduction and clinical response. However, Ghielmini et al 61 performed a double-blind and placebo RCT for NSCLC patients whose chemotherapy regimen included cisplatin and etoposide. They reported that there was no significant difference in regard to hematological toxicity in their trial.…”
Section: Phytochemicals and Related Compoundsmentioning
confidence: 99%
“…Myeloprotective and immunoenhancing effects of melatonin have been demonstrated in in vitro and in vivo experimental models. 60,61 Melatonin, a potent antioxidant, plays various roles in regulating circadian rhythms, sleep, tumor growth, and ageing. For many years, it has been known that it plays an important anticancer role.…”
Section: Phytochemicals and Related Compoundsmentioning
confidence: 99%